Effect of the combined use of Esomeprazole and Imipenem against Pseudomonas aeruginosa (Bangladesh Journal of Microbiology, 2018)
Antimicrobial activity of esomeprazole (0.25 mM) and imipenem (30 μg/ml) was tested independently and in combination against planktonic and biofilm associated cells of Pseudomonas aeruginosa. Esomeprazole (0.25 mM) and imipenem (30 μg/ml) were added to broth media in test tubes to determine their effect on growth of Pseudomonas aeruginosa at 2, 4, 6, 24 and 72 hours after inoculation at 37°C. Viable bacterial counts (cfu/ml) were measured by dilution and plating on nutrient agar medium and the biomass was measured at 600 nm using a spectrophotometer. Biomasses of bacterial biofilms were determined by tube adherence assay and measuring the absorbance at 580 nm wavelength. Pseudomonas aeruginosa showed decreased growth and biomass of sessile bacteria (p0.05). Biomass of bacterial biofilms were significantly reduced after exposure to esomeprazole and imipenem compared to untreated controls (p